WHY IS PSYCHOLOGY NECESSARY IN LEARNING LANGUAGES - Qarshiboyeva Dilfuza Burliyevna (TADQIQOTLAR.UZ, 2024)
Annotation: In this article it is discussed about special features between instructors and students especially for future teachers, apart from this, it will be highly explained about importance of psychology while organizing the foreign languages lesson in an efficient way.